The Ways of the Nation: Messianic and Universalist Nationalism in Renieris, Zambelios and Paparrigopoulos - Vallianos, Pericles (The Historical Review/La Revue Historique, 2019)
The vital cultural project during the nineteenth century was the formation of an authoritative version of the national consciousness that serve to homogenise the disparate populations of newly independent Greece. Three towering intellectuals led the way in this process: Markos Renieris, Spyridon Zambelios and Konstantinos Paparrigopoulos. All three adhered to the since dominant theory of the historical continuity of the Greek nation from prehistoric times to the present but held sharply different views concerning the role of Greece in the modern world. Renieris stressed the European vocation of today’s Hellenic culture, given that the foundations of European civilisation were initially Hellenic as well. Zambelios put forward an anti-Western view of the nation’s destiny, tinged with theological fanaticism and a mystical historicism. Paparrigopoulos was the consummate historian who emphasised the links between the Greek present and the past, chiefly through the medium of language, but without hiding the sharp discontinuities between historical periods.